Spatiotemporal dynamics and heterogeneity of renal lymphatics in mammalian development and cystic kidney disease - Daniyal J Jafree; Dale Moulding; Maria Kolatsi-Joannou; Nuria Perretta Tejedor; Karen L Price; Natalie J Milmoe; Claire L Walsh; Rosa Maria Correra; Paul JD Winyard; Peter C Harris; Christiana Ruhrberg; Simon Walker-Samuel; et al. (eLife, 2019)
Heterogeneity of lymphatic vessels during embryogenesis is critical for organ-specific lymphatic function. Little is known about lymphatics in the developing kidney, despite their established roles in pathology of the mature organ. We performed three-dimensional imaging to characterize lymphatic vessel formation in the mammalian embryonic kidney at single-cell resolution. In mouse, we visually and quantitatively assessed the development of kidney lymphatic vessels, remodeling from a ring-like anastomosis under the nascent renal pelvis; a site of VEGF-C expression, to form a patent vascular plexus. We identified a heterogenous population of lymphatic endothelial cell clusters in mouse and human embryonic kidneys. Exogenous VEGF-C expanded the lymphatic population in explanted mouse embryonic kidneys. Finally, we characterized complex kidney lymphatic abnormalities in a genetic mouse model of polycystic kidney disease. Our study provides novel insights into the development of kidney lymphatic vasculature; a system which likely has fundamental roles in renal development, physiology and disease.